1991
DOI: 10.1136/bmj.303.6798.333
|View full text |Cite|
|
Sign up to set email alerts
|

Review of neonatal screening programme for phenylketonuria.

Abstract: Objective-To review the neonatal screening programme during 1984-8. Design-Analysis of data from screening laboratories and paediatricians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 9 publications
0
39
0
2
Order By: Relevance
“…Other non-traditional therapies are also being used such as large neutral amino acids (LNAA) which have shown to be beneficial in maintaining low phenylalanine levels in the body without the need of dietary control ) and other therapies that are still under experimentation such as gene therapy, enzyme replacement therapy and cell transplantation (Mitchell et al 2011;van Spronsen and Enns 2010). The licence committee were satisfied that our revised application provided clarification on the likelihood of PKU being detected in the newborn: there is a neonatal screening programme in the UK to test all newborns at 6-14 days, but it has been shown that there are regional variations in the timing of this test and the time of starting treatment, with about 8% of newborns with severe PKU still not treated by 20 days after birth (Smith et al 1991). After studying our revised application and correspondence from the NSPKU, the licensing committee concluded that even if the condition is detected at birth and is treated immediately, the lifelong dietary regime and medication in the child can be seriously intrusive and socially and psychologically invasive and damaging.…”
Section: Discussionmentioning
confidence: 99%
“…Other non-traditional therapies are also being used such as large neutral amino acids (LNAA) which have shown to be beneficial in maintaining low phenylalanine levels in the body without the need of dietary control ) and other therapies that are still under experimentation such as gene therapy, enzyme replacement therapy and cell transplantation (Mitchell et al 2011;van Spronsen and Enns 2010). The licence committee were satisfied that our revised application provided clarification on the likelihood of PKU being detected in the newborn: there is a neonatal screening programme in the UK to test all newborns at 6-14 days, but it has been shown that there are regional variations in the timing of this test and the time of starting treatment, with about 8% of newborns with severe PKU still not treated by 20 days after birth (Smith et al 1991). After studying our revised application and correspondence from the NSPKU, the licensing committee concluded that even if the condition is detected at birth and is treated immediately, the lifelong dietary regime and medication in the child can be seriously intrusive and socially and psychologically invasive and damaging.…”
Section: Discussionmentioning
confidence: 99%
“…7 The overall incidence of PKU in the UK is 7-11/100 000 or 1 in 10-15 000 live births. 8,9 A universal screening programme for PKU was introduced in the 1960s. Data available in the UK over a 30-year period (1964-93) revealed 2259 infants with PKU, of whom 976 (43.2%) were females (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…National neonatal screening for phenylketonuria began in 1969 and other conditions have been added [11][12][13]. These programmes aim at 100% coverage at an early age and every live born baby should have a completed screening test by 20 days of age [11].…”
Section: Introductionmentioning
confidence: 99%
“…These programmes aim at 100% coverage at an early age and every live born baby should have a completed screening test by 20 days of age [11]. However, uptake of testing (coverage) is often incomplete [11,12,14,15], with differential coverage in ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation